2021
DOI: 10.3390/molecules26175238
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Fumonisin B1 Contamination and Toxicity: A Review

Abstract: Fumonisin B1 (FB1), belonging to the member of fumonisins, is one of the most toxic mycotoxins produced mainly by Fusarium proliferatum and Fusarium verticillioide. FB1 has caused extensive contamination worldwide, mainly in corn, rice, wheat, and their products, while it also poses a health risk and is toxic to animals and human. It has been shown to cause oxidative stress, endoplasmic reticulum stress, cellular autophagy, and apoptosis. This review focuses on the current stage of FB1 contamination, its toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 154 publications
0
46
0
3
Order By: Relevance
“…4 Intraday repeatability measured on 12 samples spiked before extraction with 6250 pmol/g liver or 1563 pmol/mL plasma. 5 Interday repeatability measured on 4 consecutive days in 3 samples per day spiked before extraction with 6250 pmol/g liver or 1563 pmol/mL plasma. a = slope of the calibration curve; R 2 = coefficient of determination; SSE = signal suppression and enhancement; RA = apparent recovery; R = recovery; RSD = relative standard deviation.…”
Section: Validation Of the Methods On Ismentioning
confidence: 99%
See 1 more Smart Citation
“…4 Intraday repeatability measured on 12 samples spiked before extraction with 6250 pmol/g liver or 1563 pmol/mL plasma. 5 Interday repeatability measured on 4 consecutive days in 3 samples per day spiked before extraction with 6250 pmol/g liver or 1563 pmol/mL plasma. a = slope of the calibration curve; R 2 = coefficient of determination; SSE = signal suppression and enhancement; RA = apparent recovery; R = recovery; RSD = relative standard deviation.…”
Section: Validation Of the Methods On Ismentioning
confidence: 99%
“…Fumonisins are mycotoxins produced by fungi of the genus Fusarium that are found worldwide [1][2][3][4][5]. Among the different groups of fumonisins identified, fumonisin B (FB), and in particular fumonisin B1 (FB1) and fumonisin B2 (FB2), are the most widespread and the most frequently studied [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the toxicity of FB1 has aroused widespread public concern [13]. Several studies have shown that FB1 can pose many toxic effects (neurotoxic, hepatotoxic and nephrotoxic) in humans [9,14,15]. The International Agency for Research on Cancer (IARC) classified FB1 as group 2B (possible carcinogenic to humans), since there is no direct established causal association between FB1 exposure and cancer in humans (IARC, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They primarily contaminate corn (maize), corn-derived products, asparagus, sorghum, beer, rice, soybeans, and animal feed, as well as the food chain, threatening to food safety and minimizing animal production ( 1 4 ). According to recent estimates, 60–80% of mycotoxin contamination occurs naturally in food and feed, posing a risk to human and animal health worldwide ( 5 ). Mycotoxins can enter the human body directly through the consumption of plant-based foods with primary contamination or indirectly through the transfer of toxins and their metabolites into animal-derived products (milk, meat and eggs) with secondary contamination.…”
Section: Introductionmentioning
confidence: 99%